Zmysł dotyku w cieniu wersów: poezja Marii Pawlikowskiej‑Jasnorzewskiej i Anny Achmatowej - Trojanowska, Beata (Slavia Orientalis, 2026)
This article seeks to juxtapose selected poetic works by Maria Pawlikowska‑Jasnorzewska and Anna Akhmatova in terms of their modes of expressing corporeality and sensuality — with particular emphasis on the role of touch. In poetry, and especially in love lyrics, touch emerges as a remarkably potent vehicle of expression: it amplifies emotional resonance, intensifies intimacy, and endows lyrical relationships with a sensual dimension. The aim of the study is to highlight both areas of convergence and the marked differences in the ways each poet engages with this motif, while taking into account their distinct poetic codes. The theoretical framework of the discussion draws, among others, on concepts formulated by Mikhail Epstein — the Russian‑American philosopher, literary scholar, and cultural theorist — as presented in his work Philosophy of the Body, published in Russian in 2007. The analysis of selected texts from the early stages of both poets’ creative output allows for the formulation of a thesis that the sense of touch, within the amorous and erotic code, constitutes a crucial determinant in shaping the feelings and emotions of the female lyrical subject. Touch establishes specific relations between the lyrical subject and the male figure, where — alongside traditional poetic imagery of the tactile sphere, typically dominated by the male perspective — one also encounters instances of female haptic agency, which serve to expose culturally ingrained stereotypes of social perception. Touch thus becomes a formative element in the construction of lyrical identity, “reflecting the constant oscillation between closeness and distance, resignation and rebellion,” while simultaneously blurring the boundaries between the conscious, the spiritual, the emotional, and the corporeal. In Pawlikowska‑Jasnorzewska’s poetry, depictions of touch that convey the lyrical subject’s love and erotic fascinations combine intimacy with intellectual play, lay bare the absurdities of everyday life and social conventions, and at times reveal the poet’s ironic distance toward herself. Yet within this touch resides the hope of fulfilment, of a happy union — a dimension absent from Akhmatova’s lyrics, in which the man’s touch conceals a certain falseness, an insincerity of feeling, and whose gestures foreshadow an imminent separation that brings pain and disappointment to the lyrical subject.